2009
DOI: 10.1002/app.31661
|View full text |Cite
|
Sign up to set email alerts
|

Comparative delivery of Diltiazem hydrochloride through synthesized polymer: Hydrogel and hydrogel microspheres

Abstract: In this study, interpenetrating polymer network (IPN) hydrogel based on polyvinyl alcohol (PVA) networking with polyacrylic acid (PAA) were prepared by a non-conventional emulsion method without any added crosslinker, using benzoyl peroxide as initiator and sodium chloride (NaCl) as additive. The IPN hydrogel was characterized by using Fourier transformed infrared (FTIR) spectrophotometry, Thermo gravimetric analysis (TGA), and Scanning electron microscopy (SEM). (PVA-co-PAA)/ NaCl normal IPN hydrogel (H) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Other formulations gave n values between 0.695 and 0.985 (i.e., 0.5 < n < 1) indicating that the release mechanism of DTZ HCl from these matrices was anomalous (non-Fickian), which suggested that both diffusion of the drug in the hydrated matrix and its erosion modulated drug release. Similar results were obtained in the release of DTZ HCl from polyvinyl alcohol-polyacrylic acid microspheres (30) and EE-carbopol PEC tablets (16).…”
Section: Kinetics Of Drug Releasesupporting
confidence: 84%
“…Other formulations gave n values between 0.695 and 0.985 (i.e., 0.5 < n < 1) indicating that the release mechanism of DTZ HCl from these matrices was anomalous (non-Fickian), which suggested that both diffusion of the drug in the hydrated matrix and its erosion modulated drug release. Similar results were obtained in the release of DTZ HCl from polyvinyl alcohol-polyacrylic acid microspheres (30) and EE-carbopol PEC tablets (16).…”
Section: Kinetics Of Drug Releasesupporting
confidence: 84%
“…Additionally, the carboxylate anions cause more hydrophilicity and electrostatic repulsion to the polymer segments in the hydrogel. So, by the increase in pH, the AA–PVA hydrogels swelled speedily due to more swelling driving force caused by the electrostatic repulsion between the ionized carboxylate groups [ 23 25 ]. Manifestation of the swelling ratios (dynamic and equilibrium) of AA–PVA hydrogels is given in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Ray et al prepared an IPN hydrogel based on PVA networking with PAA (PVA-co-PAA)/NaCl microspheres. The hydrogels were loaded with diltiazem hydrochloride (DL) and showed comparatively higher DL entrapment (79%), better control over DL release up to 24 h, and were more effective in reducing blood pressure to 40.1% [98]. Josef et al investigated a composite gel system formulated from microemulsions (ME) embedded in alginate hydrogels.…”
Section: Drug Deliverymentioning
confidence: 99%